1997
DOI: 10.1210/jcem.82.2.3769
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Cortisol Rhythms in Healthy Boys and Girls: Relationship with Age, Growth, Body Composition, and Pubertal Development1

Abstract: To provide basic information on the normal functioning of the hypothalamus-pituitary-adrenal axis in relation to pubertal development, growth (weight and height), body composition, and gender and to obtain reference data for serum cortisol concentrations in children, we investigated the basal circadian rhythm of serum cortisol in a group of 235 healthy children (162 boys and 73 girls). The age range was between 2.2-18.5 yr. Serum cortisol was analyzed from venous blood samples taken at 1400, 1800, 2200, 0200, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…In the present study the salivary cortisol concentrations of both groups tended to follow previously reported diurnal variation (35,36), indicating normally functioning HPA axes. Salivary cortisol concentrations in the LN and OB groups were highest in the morning, reached low points in the early afternoon (1200 -1300 h), and rose in response to lunch.…”
Section: Salivary Cortisolsupporting
confidence: 83%
“…In the present study the salivary cortisol concentrations of both groups tended to follow previously reported diurnal variation (35,36), indicating normally functioning HPA axes. Salivary cortisol concentrations in the LN and OB groups were highest in the morning, reached low points in the early afternoon (1200 -1300 h), and rose in response to lunch.…”
Section: Salivary Cortisolsupporting
confidence: 83%
“…serum or saliva, the relation between age and cortisol concentrations has yielded conflicting results. Knutsson et al [12] found no effects of age on serum cortisol in a study in 235 healthy children. However, two larger studies on serum cortisol in 762 and 1,482 healthy children aged 0-18, respectively, reported high cortisol variance in neonates and infants, after which cortisol rapidly decreased to subsequently increase steadily with age up to adulthood [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Mean (range) age was 10.8 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years. The criteria for this diagnosis are exclusion of an organic cause and fulfilling six out of the following seven criteria: 1. onset or aggravation of chronic negative stress at the time of onset of recurrent pain; 2. pain in parallel with chronic negative stress; 3. feeling better or pain-free during periods of lessened/no chronic negative stress; 4. pain induced by acute stress"; 5. most pain attacks related to acute stress; 6. the child followed up for at least 1 year; 7. parent/child and responsible doctor agree about the diagnosis 5 .…”
Section: Rap Groupmentioning
confidence: 99%